2018
DOI: 10.1155/2018/9703754
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Vulvovaginal Candidiasis among Women of Reproductive Age in Xi’an: A Cross-Sectional Study

Abstract: Purpose. To explore risk factors of vulvovaginal candidiasis (VVC) among women of reproductive age in Xi'an district and then to offer reference for clinical prevention and treatment of VVC. Methods. Patients from the outpatient department of gynecology and obstetrics in the First Affiliated Hospital of Xi'an Jiaotong University from June 2016 to May 2017 were recruited strictly according to the inclusion and exclusion criteria. Participants diagnosed as simple VVC were assigned to the case group, while women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
4
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 30 publications
(34 reference statements)
6
75
4
7
Order By: Relevance
“…VVC represents one of the most frequent infections of the genital tract affecting millions of women each year [2]. Several studies evaluating the prevalence of candidiasis among pregnant women showed that the distribution of isolated Candida species varies between countries, and it is greatly depending on several risk factors such as age, hygienic habits, and disease history [2, 6, 10, 16]. To the best of our knowledge, this is the first study investigating the prevalence of vaginal candidiasis among pregnant women in Lebanon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VVC represents one of the most frequent infections of the genital tract affecting millions of women each year [2]. Several studies evaluating the prevalence of candidiasis among pregnant women showed that the distribution of isolated Candida species varies between countries, and it is greatly depending on several risk factors such as age, hygienic habits, and disease history [2, 6, 10, 16]. To the best of our knowledge, this is the first study investigating the prevalence of vaginal candidiasis among pregnant women in Lebanon.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors related to physiologic changes, such as decreased cellular immunity, elevated hormone levels, reduced vaginal pH, and increased vaginal glycogen concentration, have been associated with a higher risk of VVC during pregnancy [6, 9, 10]. Candida colonization is also considered to be a consequence of broad-spectrum antibiotic use and has been reportedly associated with a decreased colonization of Lactobacillus , probably resulting from the interference with epithelial binding sites [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, reports showed that significant percentage of healthy women harbour species of Candida in their genital tract (Makanjuola et al, 2018). Other risk factors may include indulgence in sugary, diets, sedentary lifestyle, and abuse of antibiotics (Zeng et al, 2018). In their quest for the predilection of C. albicans in the vulvovaginal tract, Amabebe and Anumba (2018), suggested that although glycogen accumulation in vagina of post reproductive women population consists in one of the hormonal effects of estrogen, the influence of stress on the pituitary hormone can also, ultimately trigger accumulation of glycogen and susceptibility to colonization by C. albicans and subsequent infection in the pre-reproductive women.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of these will have a second episode, and 5 to 10% will develop the recurrent form. 2 Vulvovaginal candidiasis gives rise to much discomfort in many patients, poses a threatening problem to clinicians, and generates considerable direct and indirect economic costs associated with medication and healthcare visits, 3 representing a cost estimate of $2.84 billion in the United States alone. 4 Most women will experience only one or two episodes of VVC, but there is a large, albeit poorly defined, subset that experiences multiple recurrences.…”
Section: Introductionmentioning
confidence: 99%